GAMBAR WAYANG KARYA SURIPNO DARI PERSPEKTIF RASA DALAM KEBUDAYAAN JAWA - Widiyanto, Feri (Institut Seni Indoensia Surakarta, 2018)
ABSTRACTÂ Wayang purwa is a Javanese art and culture product. The existence of wayang purwa in Javanese culture is very influential on the life of Javanese society. Variants of wayang that can be found today is one of them is a puppet image made by Suripno. The process of creating Suripno puppet shapes also can not be separated from the experience and knowledge of Suripno as the maker. The method used in this study is an ethnographic method that emphasizes the observation of behavior, interviews and artifacts.Suripno's wayang pictures are an expression of his inward appreciation to the characters, mythology and the wayang story. Viewed from the perspective of taste in the Javanese culture aesthetics Suripno puppet pictures are a non-sensory aesthetic based on sense of appreciation, protection, tranquility, evenness and irony.Â Keywords: Suripno, puppet image, aesthetics, taste, Javanese culture.